Troubleshooting Java : read, debug, and optimize JVM applications - Spilcă, Laurenţiu (Manning Publications, 2023)
Fact: Over the course of your career, you'll spend far more time reading code than you will writing it. The code investigation skills in this book will radically improve your efficiency in understanding and improving Java applications. "Troubleshooting Java: read, debug, and optimize JVM applications" presents practical techniques for exploring and repairing unfamiliar code. In it, you'll learn timesaving practices for discovering hidden dependencies, discovering the root causes of crashes, and interpreting unexpected results. Go beyond profiling and debugging and start understanding how Java applications really work.